Speculative Transitions: Hegel, John Huston’s Moby Dick and the Dissolve - Joshua Harold Wiebe (Film-Philosophy, 2025)
This article draws out a potential encounter between Hegel and film studies. Following a line of thought instantiated by Theodor Adorno, it constructs a method of reading Hegel through cinematic formal analysis. In particular, the article argues that the speculative proposition should be thought through the structure of the dissolve. The speculative proposition is a sentence whose subject and predicate rest in uneasy relation to one another, and which is not a proposition of simple identity. Making use of a famous example from The Phenomenology of Spirit, the article elaborates the confused position of the speculative proposition and demonstrates the necessity of explanatory tools that approach the matter obliquely. In the process of making this argument, other attempts to put dialectics and montage together (notably, Eisenstein’s) are situated in relation to the instructional potential of the dissolve. Close reading of a particular dissolve taken from Moby Dick (John Huston, 1956) demonstrates the isomorphism between the mechanism of Hegelian dialectic and this particular unit of film form. The article concludes by returning to a particular speculative proposition in light of the insights gleaned from formal analysis.